Population structure and antimicrobial resistance among Klebsiella isolates sampled from human, animal, and environmental sources in Ghana:a cross-sectional genomic One Health study - Calland, Jessica K.; Haukka, Kaisa; Kpordze, Stephen W.; Brusah, Atanyiwoen; Corbella, Marta; Merla, Cristina; Samuelsen, Ørjan; Feil, Edward J.; Sassera, Davide; Karikari, Akosua B.; Saba, Courage K.S.; Thorpe, Harry A.; et al. (The Lancet Microbe, 2023)
Background: One Health approaches to address the increasing threat of antimicrobial resistance (AMR) are gaining attention. However, data on the distribution and movement of bacteria and their AMR-associated genes between clinical and non-clinical sources are scarce, especially from low-income and middle-income countries. We aimed to analyse Klebsiella isolates from various sources in Ghana and compare the prevalence of AMR with datasets from two other countries. Methods: We conducted a cross-sectional genomic One Health study. Multiple clinical, environmental, and animal sources were sampled from 78 locations (eg, hospitals, residential areas, and farms) in and around Tamale, Ghana. Clinical samples were collected through routine screening and in cases of suspected infection between March 15 and Sept 15, 2019, and samples from the wider environment were collected during a dedicated sampling effort between the dates of Aug 19, 2018, and Sept 26, 2019. Sampling locations were approximately evenly distributed from the centre of the city and steadily outwards to capture both rural and urban locations. Samples with positive growth for Klebsiella were included. Isolates of Klebsiella were obtained from the samples using Simmons citrate agar medium and characterised by antimicrobial susceptibility testing and whole-genome sequencing. A comparative analysis with Klebsiella population surveys from Pavia, Italy, and Tromsø, Norway, was performed. AMR-associated and virulence genes were detected, and the population distribution of these genes was studied. Findings: Of 957 samples collected around Tamale, Ghana, 620 were positive for Klebsiella spp. 573 Klebsiella isolates were successfully sequenced, of which 370 were Klebsiella pneumoniae. Only two hospital isolates were carbapenem-resistant. Extended-spectrum β-lactamase (ESBL) genes were relatively common among the Ghanaian clinical isolates but rare in the environmental samples. Prevalence of ESBL genes in human—hospital disease samples was 64% (14 of 22 isolates) in ...